Does mitigating pain decrease the risk of infection? The interactions between nociception and immune function. Issue 1 (February 2015) - Hatfield, Linda A.; Umberger, Reba
Abstract Recent studies suggest that analgesic interventions may influence immune function and the development of infection in neonates. Although substantial literature exists for the bidirectional relationship between nociception and immune pathways, there is a paucity of rigorous research linking nociception and immune function with the incidence of infection. This article presents the best available evidence for the interactions between nociception, immune function and the development of infection. Rigorous research is urgently needed to determine if anesthetic and analgesic regimens can influence immunomodulation or boost immune function significantly to avert infection.